Acetylcholine Attenuates Hypoxia/Reoxygenation Injury by Inducing Mitophagy Through PINK1/Parkin Signal Pathway in H9c2 Cells. Issue 5 (23rd October 2015) - Sun, Lei; Zhao, Mei; Yang, Yang; Xue, Run‐Qing; Yu, Xiao‐Jiang; Liu, Jian‐Kang; Zang, Wei‐Jin
Abstract : Acetylcholine (ACh) protected against cardiac injury via promoting autophagy and mitochondrial biogenesis, however, the involvement of mitophagy in ACh‐elicited cardioprotection remains unknown. In the present study, H9c2 cardiomyocytes were subjected to hypoxia/reoxygenation (H/R) and ACh treatment during reoxygenation. Mitophagy markers PTEN‐induced kinase 1 (PINK1) and Parkin translocation were examined using western blot and confocal fluorescence microscopy. Mitochondrial membrane potential and reactive oxygen species (ROS) were detected with fluorescence staining. We found that H/R‐treated cells exhibited reduced levels of PINK1 and Parkin in mitochondria, accompanied with decreased autophagy flux (reduced LC3‐II/LC3‐I and increased p62). Conversely, ACh increased PINK1 and Parkin translocation to mitochondria and enhanced autophagy proteins. Confocal imaging of Parkin and MitoTracker Green‐labeled mitochondria further confirmed ACh‐induced mitochondrial translocation of Parkin, which was reversed by M2 receptor antagonist methoctramine and M2 receptor siRNA, suggesting ACh could induce mitophagy by M2 receptor after H/R. Mitophagy inhibitor 3‐methaladenine abolished ACh‐induced mitoprotection, manifesting as aggravated mitochondrial morphology disruption, ATP and membrane potential depletion, increased ROS overproduction, and apoptosis. Furthermore, PINK1/Parkin siRNA attenuated the protective effects of ACh against ATP loss and oxidative stress due to mitochondrial‐dependent injury. Taken together, ACh promoted mitochondrial translocation of PINK1/Parkin to stimulate cytoprotective mitophagy via M2 receptor, which may provide beneficial targets in the preservation of cardiac homeostasis against H/R injury. J. Cell. Physiol. 231: 1171–1181, 2016. © 2015 Wiley Periodicals, Inc.